MRI findings of ischiofemoral impingement after total hip arthroplasty are associated with increased femoral antetorsion. (July 2022) - Fischer, Tim; Stern, Christoph; Fritz, Benjamin; Zingg, Patrick O; Pfirrmann, Christian WA; Sutter, Reto
Background: Ischiofemoral impingement (IFI) is a known complication after total hip arthroplasty (THA). Purpose: To assess if increased postoperative (FA) is associated with magnetic resonance imaging (MRI) findings of IFI. Material and Methods: In 221 patients with THA, two independent readers measured FA, ischiofemoral space (IFS), quadratus femoris space (QFS), edema, and fatty infiltration of quadratus femoris muscle. Three sets of IFI-imaging features were defined: acute IFI (set 1): IFS ≤15 mm or QFS ≤10 mm and edema in the quadratus femoris muscle; chronic IFI (set 2): IFS ≤15 mm or QFS ≤10 mm and fatty infiltration of quadratus femoris muscle Goutallier grade ≥2; acute and chronic IFI (set 3) with both criteria applicable. For each set, FA angles were compared between positive findings of IFI and negative findings of IFI. The t-test for independent samples tested statistical significance. Results: In 7.2% (16/221) of patients, findings of IFI (IFS ≤15 mm or QFS ≤10 mm and edema, n = 1; fatty infiltration, n = 9; or both, n = 6) were observed. In women, 11.4% (14/123) exhibited findings of IFI compared to 2.0% (2/98) in men. Comparison in set 1 (n = 7): mean antetorsion of 23.9° ± 9.8° (findings of acute IFI) compared to 14.4° ± 9.7° ( P = 0.01). Comparison in set 2 (n = 15): mean antetorsion of 16.2° ± 6.3° (findings of chronic IFI) compared to 14.5° ± 9.9° ( P = 0.49). Comparison in set 3 (n = 6): mean antetorsion of 20.4° ± 3.8° (findings of acute and chronic IFI) compared to 14.5° ± 9.9° ( P = 0.01). Conclusion: After THA, high postoperative FA is associated with MRI findings of acute as well as acute and chronic IFI. Findings of IFI were commonly seen in women.